STRATEGI KOPING STRESS PADA WANITA USIA DEWASA MADYA YANG BELUM MENIKAH - Mitchikko I. G. Rau; Mozes M. Wullur; Gloridei L. Kapahang (PSIKOPEDIA, 2022)
The purpose of this study is to find a more precise picture of the focus of the study on coping strategies for unmarried young adult women. This study uses qualitative research methods, this type of research is descriptive research of one type in qualitative methods because the analysis does not use numbers. The subject in this study was one unmarried young adult woman who was domiciled in Kaskasen II, Ling. VIII, Kec. North Tomohon, Tomohon City. The sampling method used in this study was purposive sampling. Based on the results of the study, there are two influences on the occurrence of stress, namely internal and external factors (internal). The way the subject is used to avoid stress is to do coping strategies. Coping strategies are attempts to control, reduce, or learn to tolerate stressful situations that lead to stress. This study found various types of coping centered on the problems used by the subject and led to problem solving or eliminating problems that cause stress participants. The subject does not take aggressive action to eliminate the source of the problem or pressure, only the subject utters aggressive sentences. Then the subject also manages his feelings to manage the stress he's facing. In addition, this self-control is a form of adaptation or adjustment to the pressures experienced by the subject. The process of making distance is also carried out by the subject to avoid problems. One of the actions taken by the subject is to be rarely at home and spend a lot of time outside and to find yourself busy.